OPTIMALISASI PERAN MASJID SUNAN KALIJAGA DALAM PENGEMBANGAN RELIGIULITAS MASYARAKAT DESA KERTOSUKO KECAMATAN KRUCIL KABUPATEN PROBOLINGGO - Moch Yunus; Ainur Rofiq Sofa; Riris Usmawati (Najah: Journal of Research and Community Service, 2023)
This study aims to analyze the optimization of the role of Sunan Kalijaga Mosque in developing the religiosity of the community in Kertosuko Village, Krucil District, Probolinggo Regency. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation involving mosque administrators, religious leaders, mosque youth, and congregants as informants. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that Sunan Kalijaga Mosque plays a significant role in enhancing community religiosity through three main aspects: worship, religious education, and socio-religious activities. The optimization of the mosque’s role is supported by strong backing from religious and community leaders, deeply rooted religious traditions, and congregants’ awareness of the mosque’s importance as a center for religious development. However, limitations in human resources, insufficient funding, and the lack of long-term program planning hinder the sustainable development of the mosque’s role. This study concludes that strengthening mosque management and strategic planning is essential to enable mosques to function more optimally in fostering the religiosity of rural communities.